Public Communication Strategy Of The Government In Minimizing The Impact Of The Transmission Of Covid-19: Strategi Komunikasi Publik Pemerintah Dalam Meminimalisir Dampak Dari Penularan Covid-19 - Dwi Prasetya, Andrean; Hariyanto, Didik (Indonesian Journal of Public Policy Review, 2022)
This study examines how the public communication strategy of the Sidoarjo district government in minimizing the impact of Covid-19 transmission in Sidoarjo. This study uses the theory of communication strategy and public communication. The purpose of this study was to determine the communication strategy of the Sidoarjo district government in minimizing the impact of the transmission of COVID-19 in Sidoarjo. The research is descriptive and the research method used is qualitative with data collection techniques using interviews consisting of 5 people. The results of research that have been carried out on the public communication strategy of the Sidoarjo Regency government in minimizing the impact of the transmission of covid-19 in Sidoarjo are shown to the public, but in general on people's behavior in complying with health protocols, the public can also receive message information from various sources such as online media Instagram. , web and facebook. And also through print media such as banners, posters and billboards, the community also gets information about prevention and minimizing the impact of Covid-19 transmission from village socialization.